2009
DOI: 10.2147/ce.s5995
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of palifermin (keratinocyte growth factor-1) in the amelioration of oral mucositis

Abstract: Purpose: Oral mucositis is a significant toxicity of cytotoxic chemo-and radiation-therapy used to treat cancer. Palifermin is the first pharmaceutical/biological agent approved for the intervention of oral mucositis. The major objective of this review is to evaluate the evidence supporting the use of palifermin. Methods: A literature search was performed using an appropriate keyword search in MEDLINE and PubMed databases. Results: Of 100 full papers and 4 abstracts identified, 12 papers and 3 abstracts were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 21 publications
0
36
1
1
Order By: Relevance
“…19 In the control groups of present study, statistical analysis at day four and eight showed that there was nonsignificant differences (P >0.05) present between the Saline/Water treated group and the Saline/ Ascorbic acid group regarding the epithelial thickness, damage scores, and rate of proliferation. Complementary and alternative medical practitioners worldwide currently use ascorbate intravenously in patients, in part because there are no apparent harmful effects.…”
Section: Discussioncontrasting
confidence: 44%
“…19 In the control groups of present study, statistical analysis at day four and eight showed that there was nonsignificant differences (P >0.05) present between the Saline/Water treated group and the Saline/ Ascorbic acid group regarding the epithelial thickness, damage scores, and rate of proliferation. Complementary and alternative medical practitioners worldwide currently use ascorbate intravenously in patients, in part because there are no apparent harmful effects.…”
Section: Discussioncontrasting
confidence: 44%
“…33 In comparison with palifermin, NAC is relatively inexpensive and has no considerable interactions with antineoplastic drugs. [34][35][36][37] In our study, the overall duration of OM was also significantly shorter in the NAC group whereas in Jahangard-Rafsanjani et al 9 study, only the mean duration of severe OM (grade 3-4) was significantly lower in the intervention group (selenium). However, none of the agents could alter time to onset of OM.…”
Section: Discussionmentioning
confidence: 50%
“…Extrinsic factors, such as smoking and alcohol abuse during radiotherapy and/or chemotherapy, may lead to the development of exuberant lesions and, when associated with fungal infections and poor oral hygiene, mucositis is considered as severe and may require partial or complete discontinuation of radiotherapy prior to the completion of the planned protocol, which negatively affects the patient prognosis (3,4,13). Of note, ~11% of cases of discontinuation and modification of the radiotherapy regimen occur due to the development of severe oral mucositis, with the need of treatment redesign and, in some cases, patient hospitalization (8). In addition to the association of oral mucositis with a worse patient prognosis due to the potential discontinuation of chemotherapy and/or radiotherapy, infection of the lesions by opportunistic microorganisms may lead to bacteremia (4).…”
Section: Background/literature Reviewmentioning
confidence: 99%